Two Years Retrospective Study of Medicolegal Cases at Sir Salimullah Medical College, Dhaka - Rojy, Nazmun Nahar; Saha, Sejuti; Hossain, Md Abir; Sharmin Rahman Linda (The Journal of Ad-din Women's Medical College, 2026)
Background: Medicolegal cases of sexual offenses encompass behaviours such as verbal sexual harassment, compulsion, and forced penetration. Sex related crimes are the most heinous and degrading of all the crimes. The most vulnerable demographic to this crime is still women and children. A significant public health issue is the startling increase in the incidence of sexual assault on a global scale. Objective: The current study's goal was to identify the medicolegal findings of sexual offenses victims in order to highlight the procedure's obvious flaws. Materials and Methods: The data acquired from Sir Salimullah Medical College, Hospital between January 2022 and December 2023 was prepared rigorously. Informed written consent, four copies of passport-size photos, the victim herself, the authority's requisition, and a third-person female attendant, collected information on 166 victims, including the cause, location, time, and date of the examination. Results: 61.5% of the patients were between the ages of 11 and 20. 130 cases (80.2%) out of 162 were unmarried. The majority were students (44.6%) and housewives (20.5%). Significant monthly variations were discovered by the study, with January, March, and April showing the highest values. Conclusion: Collectively, evidence is a crucial responsibility for doctors. Insufficient medical evidence frequently contributes to a low conviction rate. Because of this, it is vitally important to conduct a proper and suitable physical examination in situations of sexual offenses, and the analysis of preserved biological specimens like blood and semen frequently provides essential evidence in modern criminal investigations. The Journal of Ad-din Women's Medical College; Vol. 13 (2), July 2025; p 26-30